Factorial Validity of the Anxiety Questionnaire for Students (AFS): Bifactor Modeling and Measurement Invariance. (September 2019) - Lohbeck, Annette; Petermann, Franz
The present study with 2, 273 students aimed to examine the factorial validity of the Anxiety Questionnaire for Students (AFS) by using the bifactor modeling framework, that is, contrasting a confirmatory factor analysis (CFA) model to an exploratory structural equation model (ESEM) and two bifactor models (B-CFA and B-ESEM). In addition, measurement invariance and latent mean differences in the three facets of the AFS (test anxiety, manifest anxiety, dislike of school) across gender, age groups, and school types were explored. Results provided strong support for the multidimensionality of the AFS. The B-ESEM showed the best fit to the data as opposed to the other models. Also, measurement invariance across gender, age groups, and school types was fully supported. Girls and younger students generally reported higher levels of anxiety than boys and older students, while the latter stated more dislike of school than girls and younger students. Furthermore, elementary school students showed generally higher levels of anxiety than students of the other school types.